Epstein-Barr Virus MicroRNA miR-BART5-3p Inhibits p53 Expression - Zheng, Xiang (J Virol, 2018)
Epstein-Barr virus (EBV) is the first human virus found to encode many microRNAs. It is etiologically linked to nasopharyngeal carcinoma and EBV-associated gastric carcinoma. During the latent infection period, there are only a few EBV proteins expressed, whereas EBV microRNAs, such as the BamHI-A region rightward transcript (BART) microRNAs, are highly expressed. However, how these BART miRNAs precisely regulate the tumor growth in nasopharyngeal carcinoma and gastric carcinoma remains obscure. Here, we report that upregulation of EBV-miR-BART5-3p promotes the growth of nasopharyngeal carcinoma and gastric carcinoma cells. BART5-3p directly targets the tumor suppressor gene TP53 on its 3′-untranslated region (3′-UTR) and consequently downregulates CDKN1A, BAX, and FAS expression, leading to acceleration of the cell cycle progress and inhibition of cell apoptosis. BART5-3p contributes to the resistance to chemotherapeutic drugs and ionizing irradiation-induced p53 increase. Moreover, BART5-3p also facilitates degradation of p53 proteins. BART5-3p is the first EBV-microRNA to be identified as inhibiting p53 expression and function, which suggests a novel mechanism underlying the strategies employed by EBV to maintain latent infection and promote the development of EBV-associated carcinomas. IMPORTANCE EBV encodes 44 mature microRNAs, which have been proven to promote EBV-associated diseases by targeting host genes and self-viral genes. In EBV-associated carcinomas, the expression of viral protein is limited but the expression of BART microRNAs is extremely high, suggesting that they could be major factors in the contribution of EBV-associated tumorigenesis. p53 is a critical tumor suppressor. Unlike in most human solid tumors, TP53 mutations are rare in nasopharyngeal carcinoma and EBV-associated gastric carcinoma tissues, suggesting a possibility that some EBV-encoded products suppress the functions of p53. This study provides the first evidence that a BART microRNA can suppress p53 expression by directly targeting its 3′-UTR. This study implies that EBV can use its BART microRNAs to modulate the expression of p53, thus maintaining its latency and contributing to tumorigenesis.